MORPHOLOGY AND GEOMETRY OF THE DISTAL RAMPARTS OF MARTIAN IMPACT CRATERS - Mouginis-Mark P.J.; Baloga S.M. (My University, 2006)
We used Mars Orbiter Laser Altimeter (MOLA), Thermal Emission Imaging System visible light (THEMIS VIS), and Mars Orbiter Camera (MOC) data to identify and characterize the morphology and geometry of the distal ramparts surrounding Martian craters. Such information is valuable for investigating the ejecta emplacement process, as well as searching for spatial variations in ejecta characteristics that may be due to target material properties and/or latitude, altitude, or temporal variations in the climate. We find no systematic trend in rampart height that would indicate regional variations in target properties for 54 ramparts at 37 different craters 5.7-35.9 km in diameter between 52.3°S to 47.6°N. Rampart heights for multi-lobe and single-lobe ejecta are each normally distributed with a common standard deviation, but statistically distinct mean values. Ramparts range in height from 20-180 m, are not symmetric, are typically steeper on their distal sides, and may be as much as ~4 km wide. The ejecta blanket proximal to parent crater from the rampart may be very thin (<5 m). A detailed analysis of two craters, Toconao crater (21°S, 285°E) (28 measurements), and an unnamed crater within Chryse Planitia (28.4°N, 319.6°E) (20 measurements), reveals that ejecta runout distance increases with an increase in height between the crater rim and the rampart, but that rampart height is not correlated with ejecta runout distance or the thickness of the ejecta blanket. © The Meteoritical Society, 2006.